2022
DOI: 10.7759/cureus.32598
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Mesenchymal Stem Cells for the Treatment of Evolving and Established Bronchopulmonary Dysplasia: A Systematic Literature Review

Abstract: Bronchopulmonary dysplasia (BPD) is a frequent sequela of modern medicine when infants are born prematurely. Currently, there is no single treatment or combination of treatments to prevent or fully treat BPD. Mesenchymal stem cells (MSCs) have promising properties that could aid in the reversal of lung injury, as seen in patients with BPD. This study reviews the available evidence regarding the safety and efficacy of the use of MSCs for the treatment of evolving and established BPD. This systematic review was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…There are approximately 12.7 million people on the global waiting list for corneal transplantation [21]. Corneal transplantation surgery treatments are limited due to postoperative complications such as infection and delayed healing, immune rejection and failure of the transplant, intraocular pressure elevation, and a general scarcity of donor corneas as a result of the increased popularity of laser refractive surgery [22,23] 2. Stem cell therapy: A variety of treatments have been attempted to improve scarless corneal regeneration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are approximately 12.7 million people on the global waiting list for corneal transplantation [21]. Corneal transplantation surgery treatments are limited due to postoperative complications such as infection and delayed healing, immune rejection and failure of the transplant, intraocular pressure elevation, and a general scarcity of donor corneas as a result of the increased popularity of laser refractive surgery [22,23] 2. Stem cell therapy: A variety of treatments have been attempted to improve scarless corneal regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Another study revealed that mesenchymal stem cells might restore corneal transparency by secreting hepatocyte growth factor. The ability of umbilical mesenchymal stem cell transplantation to cure corneal opacity in the congenital mice model but not in the acquired [22].…”
Section: Introductionmentioning
confidence: 99%